GERIATRIC SYNDROME EMERGENCY SCREENING USING COMPREHENSIVE GERIATRIC ASSESSMENT INSTRUMENTS - Firdausi, Nugrahaeni; Widhi Sumirat (Pedagogic Research-Applied Literacy Journal, 2024)
An elderly person is someone who has reached the age of 60 years and above, both men and women. Naturally, elderly people experience the aging process, which is characterized by a decrease in physical and psychological abilities, and an increased risk of disease or health problems that lead to death. This means that the health problem that is often found in the elderly and is multipathological is the emergency geriatric syndrome. Comprehensive Geriatric Assessment (CGA) screening results show the nutritional status, functional status, social status, cognitive status and mental status of the elderly. Comprehensive Geriatric Assessment (CGA) is used by health workers to carry out a comprehensive assessment of the elderly from biological, cognitive, psychological and social aspects to determine problems and plan management for the elderly.